Mortgage finance in Nigeria : book one - Onuigbo, Okonkwo (Aba, Nigeria: Esqurie Press, 1999)
The book reviews the history of mortgage finance, the appraisal of problems and prospects and provides the updated information on the development of mortgage finance in Nigeria.
Includes index.
A text in Mortgage banking inNigeria
rua 25/11/16, ijb 11/03/2019
Loans
Keywords: Mortgage finance; Real property - Finance; Nigeria